Ex vivo torsional properties of the Targon Vet Nail System in canine femurs: comparison with the 2.4 mm LC-DCP Plate - Macedo, Aline Schafrum [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The purpose of this study was to evaluate the torsional stability of the Targon® Vet Nail System (TVS) in small canine femurs and to study the effect of different bolt locations on the torsional strength of the constructs compared to 2.4 mm Low Contact - Dynamic Compression Plates (LC-DCP®). Thirty-six femurs were harvested from fresh small dog cadavers and allocated to 3 groups (n=12) ensuring equal bone length distribution between groups. In all bones, points 1 mm below the lesser trochanter and 1 mm above the fabellae were marked and a transverse osteotomy was performed in the middle. In group 1, the bone was fixed with the 2.5 mm TVS with the bolts applied at those pre-identified marks, leaving a 2 mm gap between fragments. In group 2, the TVS was also used but the proximal bolt was placed in a location equidistant between the proximal mark and the osteotomy, resulting in a 25% shorter inter-bolt distance. In group 3, 7-hole 2.4 mm LC-DCP® plates were applied to the lateral aspect of the bones. All constructs were tested non-destructively at a rate of 1°/sec under load control between a torque of plus and minus 0.57 Nm for 10 cycles. Cyclic loading was followed by an acute torsion to failure. The last of the 10 cycles was used to measure the deformation under non-destructive load. The stiffness and torque to failure of the constructs were measured from the final torque-deformation curves. Yield point was defined as a 1° deformation beyond the expected linear behavior of the constructs. All results were tested for normality and compared using ANOVA and Tukey post hoc tests. P values < 0.05 were considered significant. Torque at yield was 0.806 +/- 0.183 and 0.805 +/- 0.093 Nm for groups 1 and 2 and 1.737 +/- 0.461 Nm for group 3. Stiffness was 0.05 +/- 0.01; 0.05 +/- 0.007 and 0.14 +/- 0.015 Nm/° for groups 1 to 3 respectively. Displacement under cyclic loading was 16.6° +/- 2.5°; 15.6° +/- 2.1° and ...

O objetivo desse trabalho foi avaliar a estabilidade torsional do sistema Targon Vet Nail (TVS) de 2,5 mm em fêmures de cães pequenos e estudar o efeito de diferentes localizações dos bolts na força torsional das construções, comparadas a placas de baixo contato Low Contact - Dynamic Compression Plate (LC-DCP®) de 2,4 mm. Trinta e seis fêmures foram obtidos de cadáveres frescos de cães pequenos e alocados em 3 grupos (n = 12), assegurando distribuição de comprimento do osso igual entre os grupos. Em todos os ossos, o ponto 1 mm abaixo do trocânter menor e outro 1 mm acima das fabelas foram marcados e uma osteotomia transversa foi realizada equidistante a essas marcações, na diáfise. No grupo 1, o osso foi fixado com o TVS de 2,5 mm com os parafusos aplicados nessas marcas pré- identificadas, deixando um espaço de 2 mm entre os fragmentos. No grupo 2, o sistema TVS também foi utilizado, mas o parafuso proximal foi colocado num local equidistante entre a marcação e a osteotomia proximal, resultando em uma distância entre os parafusos 25% mais curta. No grupo 3, placas LC-DCP® de 2,4 mm e 7 orifícios foram aplicadas à face lateral dos ossos. Todas as construções foram testadas de forma não destrutiva a uma taxa de 1ᵒ/s sob torque controlado de mais e menos 0,57 Nm durante 10 ciclos. O teste cíclico foi seguido por uma torção aguda até ocorrer falha. O último dos 10 ciclos foi usado para medir a deformação sob carga não-destrutiva. A rigidez e torque até falha foram medidos a partir das curvas finais de torque-deformação. O limite elástico foi definido como uma deformação de 1° para além do comportamento linear esperado das construções. Todos os resultados foram testados quanto à normalidade e comparados utilizando análise de variância e teste post hoc de Tukey. Valores de P < 0,05 foram considerados significativos. Torque máximo +/- desvio padrão foi 0,806 +/- 0,183 e 0,805 +/- 0,093 Nm para...
Keywords: Cães; Biomecânica; Cirurgia veterinaria; Fixação de fratura; Ortopedia veterinaria; Biomechanics